IDENTIFIKASI BERPIKIR KRITIS STANDAR ANALISIS LEVEL KINERJA NOVICE DENGAN MODEL PEMBELAJARAN ONLINE LEARNING MODEL - Indah Rahayu Panglipur; Lutfiyah Lutfiyah (Program Studi Pendidikan Matematika, 2020)
Learning activities were carried out online or the Online Learning Model (OLM) in the era of the Covid-19 pandemic. Every student who participates in OLM is trained in critical thinking and regularly improves the solving of a mathematical problem. This research used qualitative research with a descriptive approach. Researchers were interested in identifying critical thinking standards of analysis at the Novice Performance Level with the Online Learning Model (OLM) in Geometry Lectures in solving geometric problems based on students' Critical thinking skills with analysis indicators. Subjects were taken based on the assignment score on the material. Subjects were grouped into 3 abilities, namely low ability (Re), medium ability (Se), and high ability (Ti). The number of subjects was three people who were taken from each group at each level. Data were collected using 2 mutually supporting instruments, namely the test instrument and the interview instrument. The validation used was expert validation and content validation. The results showed that online learning activities or the Online Learning Model (OLM) can be identified that subjects with low abilities fulfill all indicators in the analysis stage, while not meeting all indicators for moderate and high student abilities because the Novice performance level is in accordance with its understanding, namely the lowest level where the subject had not been able to solve the given problem at all.